2018
DOI: 10.1101/423129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mis-expression of the Alzheimer’s disease associated gene Ankyrin causes memory loss and shortened lifespan in Drosophila

Abstract: Alzheimer's disease (AD) is the most common form of dementia and is characterized by the accumulation of extracellular amyloid beta (A) plaques and intracellular neurofibrillary tangles of hyperphosphorylated Tau, including the 4R0N isoform. Recent epigenome-wide association studies (EWAS) of AD have identified a number of loci that are differentially methylated in AD cortex. Indeed, hypermethylation of the Ankyrin 1 (ANK1) gene in AD has been reported in the cortex in numerous different post-mortem brain coh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Among the hubs, TOMM22 serve as the main receptor for accumulation of amyloid β (Aβ) peptides in AD (Hu et al, 2018). Previous studies showed that the gene ANK2 is involved in AD (Higham et al, 2018). Our analysis also detected RORA as a hub which is distinctively overexpressed in the hippocampus of AD brain (Acquaah-Mensah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among the hubs, TOMM22 serve as the main receptor for accumulation of amyloid β (Aβ) peptides in AD (Hu et al, 2018). Previous studies showed that the gene ANK2 is involved in AD (Higham et al, 2018). Our analysis also detected RORA as a hub which is distinctively overexpressed in the hippocampus of AD brain (Acquaah-Mensah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing to speculate that altered tau funcCon could explain the differences in mitochondrial redistribuCon at the AIS between Cdk5α-KO and Ank2-L4 expression. Altering the acCvity of Cdk5, which is known to lead to the hyperphosphorylaCon of tau, causes mitochondrial redistribuCon into the AIS throughout the lifespan while expression of Ank2-L4, which is not known to directly cause changes in tau phosphorylaCon, only shows redistribuCon of mitochondria into the AIS at older ages when tau is known to undergo agedependent hyperphosphorylaCon (Higham et al, 2019;Pao & Tsai, 2021). It is conceivable, therefore, that impaired interacCons between tau and mitochondria may underlie the redistribuCon of mitochondria into the AIS, but more study will be required to determine if such a mechanism exists.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been demonstrated that Cdk5α-KO in Drosophila causes AIS shrinkage or absence in MB neurons, followed by local swelling of the AIS and subsequent axonal degeneraCon (Spurrier et al, 2019;Trunova et al, 2011). Moreover, expressing a dominant-interfering fragment of the Drosophila neuronal ankyrin, Ank2-L4, induces similar structural disrupCon and shrinkage of the AIS, and this is also sufficient to cause axonal degeneraCon, neuron cell loss, and increased mortality (Higham et al, 2019;Jegla et al, 2016;Spurrier et al, 2019). GeneCc experiments, however, suggested that the mechanism of AIS disrupCon by Ank2-L4 expression is disCnct from that induced by Cdk5α-KO (Spurrier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A number of epigenome-wide association studies in Alzheimer's disease patients consistently report neuropathology-associated DNA hypermethylation of ANK1 (De Jager et al, 2014;Higham et al, 2019;Lunnon et al, 2014;Smith et al, 2019a;Smith et al, 2019b).…”
Section: Ankr and Alzheimer's Diseasementioning
confidence: 99%
“…Loss of AnkR results in fragile erythrocyte membranes and hemolytic anemia (Lux et al, 1990). Intriguingly, case studies of patients with hereditary spherocytic anemia, caused by mutations in AnkR, report various neurological disturbances (Coetzer et al, 1988;McCann and Jacob, 1976;Miya et al, 2012), and a number of recent epigenome-wide association studies in Alzheimer's disease (AD) have consistently found neuropathology-associated DNA hypermethylation of ANK1 (ANK1 is the gene encoding AnkR) (De Jager et al, 2014;Gasparoni et al, 2018;Higham et al, 2019;Lunnon et al, 2014;Smith et al, 2019a;Smith et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%